(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, the concept of "educational propaganda", which has not been included in scientific circulation in our science of spirituality, its definition and description, its essence and content, its connection with other types of propagation and agitation, and its importance in the life of society are highlighted. The relevance and necessity of educational propagation is based on the realization of the goals of the development strategy of new Uzbekistan related to the field of spirituality